Coordination and Dynamic Promotion Strategies in Crowdfunding with Network Externalities. Issue 4 (27th January 2020) - Li, Zhuoxin; Duan, Jason A.; Ransbotham, Sam
Abstract : Crowdfunding, a peer‐to‐peer fundraising mechanism, solicits capital from individual backers to support entrepreneurial projects. Entrepreneurs set a funding target and deadline; the project will be funded only if it reaches this funding target by the deadline. Backers individually decide whether to contribute, but their total contributions collectively determine whether the project will be successfully funded. This study models the dynamics of backers' contributions in the presence of success uncertainty and analyzes managerial promotion strategies to maximize the likelihood of funding success. Two opposing forces affect backer decisions: backers are more likely to back a project that has already reached a greater fraction of its funding goal (positive externalities), but the backing propensity declines over time (negative deadline effects). These two competing forces give rise to a time‐dependent critical threshold of funding that a project must attain to achieve successful funding. We evaluate actionable promotion strategies (when to promote the project and how much promotion effort to spend) for entrepreneurs to dynamically manage their crowdfunding campaigns.